Thermogravimetric studies on the catalytic Pyrolysis of rice husk - Balasundram, Vekes; Norazana, Ibrahim; Ruzinah, Isha; Mohd Dinie Huhaimin, Samsudin; Rafiziana, Md. Kasmani; Mohd. Kamaruddin, Abd. Hamid; Hasrinah, Hasbullah (2017)
The main objective of the present work is to study the effect of catalyst weight loading on the catalytic pyrolysis (CP) of rice husk (RH) using thermogravimetric analysis (TGA). The pyrolysis process is conducted at a heating rate of 10 °C/min in nitrogen (N2) atmosphere flowing at 150 mL/min and heated up to 700 °C. The alumina (Al2O3) catalyst was used as the support with addition of nickel (Ni) and cerium (Ce) as promoter at fixed loading by weight percent of 20 wt % Ni: 5 wt % Ce: 75 wt % Al2O3. The feedstock samples for TGA were prepared accordingly with biomass to catalyst weight loading ratio as follows: RH-2 (1:0.05), RH-3 (1:0.10), RH-4 (1:0.15), RH-5 (1:0.20), RH-6 (1:0.50), and RH-7 (1:1). For comparison, the pyrolysis of rice husk without catalyst is determined at the same operating condition and labeled as RH-1 (1:0). The TGA-DTG curves shows that, the presence of catalyst has significant effects on the volatile matter of rice husk. Sample RH-4 (1:0.15), was found to be the optimized biomass to catalyst ratio for maximum volatile matter yield. The highest degradation of cellulose and hemicellulose is observed in Phase II for RH-4 at 46.66 %. The results in this study indicated that a proper loading amount of catalyst on rice husk is very important to maximize the yield of volatile matter.